Construction of a Microsatellites-Based Linkage Map for the White Grouper (Epinephelus aeneus). Issue 8 (1st August 2014) - Dor, Lior; Shirak, Andrey; Gorshkov, Sergei; Band, Mark R; Korol, Abraham; Ronin, Yefim; Curzon, Arie; Hulata, Gideon; Seroussi, Eyal; Ron, Micha
Abstract: The white grouper ( Epinephelus aeneus ) is a promising candidate for domestication and aquaculture due to its fast growth, excellent taste, and high market price. A linkage map is an essential framework for mapping quantitative trait loci for economic traits and the study of genome evolution. DNA of a single individual was deep-sequenced, and microsatellite markers were identified in 177 of the largest scaffolds of the sequence assembly. The success rate of developing polymorphic homologous markers was 94.9% compared with 63.1% of heterologous markers from other grouper species. Of the 12 adult mature fish present in the broodstock tank, two males and two females were identified as parents of the assigned offspring by parenthood analysis using 34 heterologous markers. A single full-sib family of 48 individuals was established for the construction of first-generation linkage maps based on genotyping data of 222 microsatellites. The markers were assigned to 24 linkage groups in accordance to the 24 chromosomal pairs. The female and male maps consisting of 203 and 202 markers spanned 1053 and 886 cM, with an average intermarker distance of 5.8 and 5.0 cM, respectively. Mapping of markers to linkage groups ends was enriched by using markers originating from scaffolds harboring telomeric repeat-containing RNA. Comparative mapping showed high synteny relationships among the white grouper, kelp grouper ( E. bruneus ), orange-spotted grouper (E. coioides ), and Nile tilapia (Oreochromis niloticus ). Thus, it would be useful to integrate the markers that were developed for different groupers, depending on sharing of sequence data, into a comprehensive consensus map.